Analisis Wacana Kritis: Tayangan Kekerasan dalam Sinetron Bernuansa Keagamaan - RIDWAN BUSTAMAM (Jurnal Dialog, 2017)
Television program has been a cultural study since a long time ago due to the fact that television is a media which is purposed to educate, to inform, to entertain, and to control the society (religion), economy, and popular cultural ceremony. There will emerge some problems when the content and the message of a program does not fit with the audience’s expectation, for instance, a religious program that has potency of conflict, controversy, and violence. All of those are categorized as breaking the rules, norm, and religious teaching. This study uses critical discourse analysis in order to examine relationship among discourse and audience, economical and political interest as well as an ideological aspect. This analysis is also utilized to examine the relationship between television and related institutions. Based on this reason, this research tries to explore religious cinema electronics on television which contains violence. KEYWORDS: discourse analysis, impressions, violence, cinema electronics, religious